(3GdaUhd GdefJNHI ef QSGdI GdCNdGbs
(3ChdgG (B:s
(3gPg Led haUhd efJNHI ef Yde GdCNdGb JTJed Ydi GcJSGH aVGjd GdfaS GdGfSGfjI hGdGLJfGH Yf QPGjdgG s
(3BNQgG (B:s
(3hGdYOd JGHY ddeMHI hGdeMHI ai gPg GdeOjfI JcJH ChdG GLd GdGTJQGc ai GdaVjdI hajeG HjfgeG hGJaGb GdQCi ai GdeHOC s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdJGSYs
(3GfXQg eY GdeNWhW Qbe (B53 (3ef faS GdHYKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK s
Keywords: (3GdadSaI hGdefWbs